Regulation and modulation of the creatine kinase system - Cao, F (2018)
Substantial evidence indicates that impaired myocardial bioenergetics play a role in the pathogenesis of various cardiovascular disorders. In particular, creatine kinase (CK) system dysfunction has been associated with heart failure, ischemia/reperfusion (I/R) injury, and doxorubicin-induced cardiotoxicity. The goal of the experiments detailed in this thesis was to determine whether cardiac CK upregulation could be of therapeutic potential in these diseases. The literature suggests that overexpressing mitochondrial creatine kinase (CK-Mt) could adversely affect mitochondria, hence experiments were undertaken to elucidate the bioenergetic phenotype of a mouse model modestly overexpressing cardiac CK-Mt. CK-Mt overexpression was found to be benign in regards to metabolism and mitochondrial respiration. The mitochondrial swelling assay showed that CK-Mt overexpression inhibits opening of the mitochondrial permeability transition pore (mPTP), which may contribute towards protection during I/R. Subsequently, CK-Mt overexpressing mice were utilized to investigate whether CK-Mt overexpression improved outcomes in an in vivo model of pressure-overload chronic heart failure. Based on echocardiography and haemodynamic analysis, CK-Mt augmentation did not significantly improve cardiac function or morphology. Biochemical assays revealed that the transgenic mice had over 90% higher CK-Mt activity and 31P-MRS study confirmed that CKMt overexpression was sufficient to restore physiological PCr/ATP ratios during heart failure, suggesting that elevated CK-Mt does not protect against pressure-overload chronic heart failure. Doxorubicin (DOX) is a potent chemotherapeutic agent whose use is limited by a dosedependent cardiotoxicity that progresses to heart failure. An in vitro model was developed in HL-1 cells to explore whether CK overexpression protected against DOX-induced cardiotoxicity. HL-1 cells were transiently transfected with muscle, brain, and mitochondrial creatine kinase (CK-M, CK-B, and CK-Mt, respectively), and a significant increase in isoenzyme-specific CK activity was confirmed. Transfected cells were challenged with 250 nM DOX for 48 hours with or without creatine, and cell death was measured by flow cytometry. Increased CK overexpression and/or creatine supplementation did not reduce DOX-induced cell death. As CK augmentation was previously found to be beneficial in various cardiac conditions, an in vitro tool was developed in HEK293 cells to investigate the transcriptional regulation of CKM and CK-Mt. Two HEK293 cell lines stably overexpressing the CK-M and CK-Mt promoter regions and luciferase reporter genes were established and validated. These cell lines were used in preliminary screens to identify potential compounds that could affect CK mRNA transcription. Sixty six compounds were screened and 12 positive hits were found. In summary, the experiments in this thesis explored the effects of overexpressing CK under physiological and pathophysiological conditions. It was found that modest overexpression of CK-Mt is safe and inhibits mPTP opening, which may attenuate cardiac damage during I/R injury. However, the current level of CK-Mt overexpression does not protect against pressureoverload heart failure nor DOX-induced cardiotoxicity. An in vitro screening model system has been developed for exploration of CK transcriptional regulators, and can be used in the future for high-throughput screening of pharmacological CK regulators that could provide potential alternative treatments for heart diseases.